Analisis Penggunaan Bahasa Kiasan dalam Cerpen “Putri” Karya Putu Wijaya - Hanisang Hanisang; Katharina Woli Namang (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Figurative languages is the way the delivery of messages indirectly or uses words that have implied meaning, not literal meaning. The goal is to give the impression more beautiful, attractive, or dramatic to an expression or sentence. Figurative language is often used in literature, poetry, proverbs and everyday Conversations to convey a deeper meaning or to express feelings in more creative ways. This Research uses a qualitative Description method. The purpose of this study analyzes the use of figurative language, especially metaphors, smiles, personification, and hyperbola, in Putu Wijaya short story. By reviewing these Elements of this style, the study aims to understand how figurative language increases the Narrative Wealth and deepening emotional relations with readers. Studies suggest that Putu Wijaya uses figurative language not only as a decorative tool but also as a means to deliver complex themes, cultural shades, and social criticism. Ultimately, this study highlights the Importance of figurative language in Literary works and its role in enriching readers experiences.